Effect of Preablation Glycemic Control on Outcomes of Atrial Fibrillation Patients With Diabetes Mellitus Following Valvular Surgery Combined With the Cox-Maze IV Procedure - Peng, Zhan; Zhao, Rui; Liu, Yuhua; Yang, Yunxiao; Yang, Xiubin; Hua, Kun (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: This study was performed to assess the effect of preablation glycemic control on atrial fibrillation recurrence rates after heart valve surgery concomitant with Cox-Maze Ⅳ ablation. Methods: Twelve-month preablation trends in glycemic control were studied. Recurrence and clinical outcome data were obtained during a mean follow-up period of 36.7±23.3 months postablation. Results: Higher glycated hemoglobin (HbA1c) at the time of ablation was associated with higher postablation recurrence rates. The cumulative atrial fibrillation recurrence-free survival of patients with HbA1c ≥7.5% at the time of operation at 12, 24, 36 and 48 months was 97.1%, 78.3%, 54.2% and 36.3%, respectively (P < 0.001), and 100%, 84.9%, 37.2% and 16.2% for patients who preoperatively had an upward trend in HbA1c , respectively(P < 0.001). Conclusion: Maintaining a downward trend in HbA1c during the 12-month period before the operation and an HbA1c value less than 7.5% at the time of the operation reduced the recurrence of AF among patients who underwent heart valve surgery concomitant with the Cox-Maze Ⅳ procedure.